2020
DOI: 10.1177/1049909120902123
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Analysis of Undergraduate Nursing Students’ Attitudes Toward Advanced Care Planning and Their Willingness to Implement

Abstract: Objective: The purpose of this study is to understand the attitude of undergraduate nursing students toward advanced care planning (ACP) and their willingness to implement ACP and to analyze its influencing factors, so as to provide evidence-based basis for life and death education and ACP-related training in colleges and universities. Methods: A total of 312 nursing undergraduates from a university in Chengdu (China) were surveyed by using general information questionnaire, attitude scale of ACP, and willingn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…In the study, 59.89% of the students had never heard of ACP, which is lower than a previous survey of awareness of ACP among adolescents at 14 to 21 years of age (72%) in America [18], but it is similar to a recent study of undergraduate nursing students (65.9%) in China [15]. The low level of awareness of ACP among university students in mainland China was mainly related to the lack of advanced medical education.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…In the study, 59.89% of the students had never heard of ACP, which is lower than a previous survey of awareness of ACP among adolescents at 14 to 21 years of age (72%) in America [18], but it is similar to a recent study of undergraduate nursing students (65.9%) in China [15]. The low level of awareness of ACP among university students in mainland China was mainly related to the lack of advanced medical education.…”
Section: Discussioncontrasting
confidence: 45%
“…However, it has been reported that university students in the rst 3 grades had a stronger willingness to participate in ACP than their seniors. This may be due to that they were younger, more premature, and did not know the di culties in the implementation of ACP in real life [15]. Secondly, 95.4% of the participants in the study had reported no religion.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations